Taxonomy of Hyphodermella: a case study to show that simple phylogenies cannot always accurately place species in appropriate genera - Shan Shen; Shi-Liang Liu; Li-Wei Zhou (IMA Fungus)
Abstract The genus is a special and crucial taxonomic rank compared with others above the species level, because a species has to be placed in a certain genus instead of any other higher ranks. With more and more new species being described, the placements of their generic position are sometimes incorrect due to the simple phylogenies resulting from inappropriate sampling. Here, we focus on the taxonomy of a small wood-inhabiting fungal genus Hyphodermella. With the most comprehensive sampling to date, the phylogenetic position of Hyphodermella within Phanerochaetaceae is rearranged by employing the same ITS and nLSU regions as in previous studies and also the ITS, nLSU, rpb1, rpb2 and tef1α regions. Three species are excluded from Hyphodermella: H. poroides is placed in a newly introduced monotypic genus Pseudohyphodermella, while H. aurantiaca and H. zixishanensis are transferred to Roseograndinia. Hyphodermella suiae is described as a new species from South China and Vietnam. Keys to eight species in Hyphodermella and five in Roseograndinia are provided. Beyond solving the taxonomic issue of Hyphodermella itself, the current study also aims to suggest that all fungal taxonomists especially beginners should keep in mind to sample as many comprehensive taxa as possible in phylogenetic analyses.